A mixed method investigation of sharing economy driven car-hailing services: Online and offline perspectives. (August 2018) - Cheng, Xusen; Fu, Shixuan; de Vreede, Gert-Jan
Highlights: We investigate online and offline service quality in car-hailing apps. We validate the relationship between service quality and loyalty in the sharing economy driven context. A mixed method approach including interview and survey is conducted. We find factors that influence online and offline service quality perception respectively. Abstract: This exploratory research investigates factors affecting online and offline service quality with respect to a sharing economy driven car-hailing commerce. It further validates the relationships between service quality, satisfaction, and loyalty in the sharing economy driven business context. Building on relevant literature and 71 qualitative interviews, we identified information congruity, competence, and empathy as key factors in online service quality. Offline service quality factors include structural assurance and platform responsiveness. These five factors were included in a model for user loyalty investigation, which was tested on data from 294 questionnaires from Chinese mobile car-hailing service users. Attitudes towards the sharing economy were validated to moderate the relationship between service quality and loyalty. This study contributes to the theoretical development of service quality management, specifically in the context of emerging sharing economy driven car-hailing mobile markets.